Work–Life Balance: A Cross-Cultural Review of Dual-Earner Couples in India and the United States. (February 2016) - Munn, Sunny L.; Chaudhuri, Sanghamitra
The Problem: Today's global workforce is rife with dual-earner couples. For dual-earner couples, finding a suitable balance between work and living is often difficult, creating a need for organizations globally to be aware of the similarities and dissimilarities that exist for dual-earner couples around the world. This article identifies the work–life issues of dual-earner couples and organizational practices in both the United States and India in an effort to help organizations effectively manage work–life policies affecting the gender role dynamics of today's multicultural organizations. The Solution: This article identifies themes within the work–life literature for dual-earner couples in India and the United States in an effort to inform human resource development (HRD) scholars and practitioners about the current state and work–life needs of dual-earner couples in both countries. It would be beneficial for HRD professionals to understand and appreciate better workplace demographics in terms of social, cultural, and legal requirements in the two countries to encourage the creation and implementation of work–life friendly policies and environments. The Stakeholders: This research benefits HRD practitioners and scholars, employers, public policy officials, and dual-earner couples employed in the United States and India. It opens the door to a better understanding of the transferability of current research to practice.